DIRECTIONS OF ACCOUNTING DEVELOPMENT IN THE DIGITAL ECONOMY (Conferencea, 2022)
The article considers the impact of the digital economy on the transformation of the methodology of the national accounting system, in particular the transition from the performance of the control function to the information content of the financial and management subsystems, based on the organization of digital technology points. The change in the educational process of training accountants is considered and methods for assessing the results of mastering the profile disciplines by students are described.